2006
DOI: 10.1242/jeb.01970
|View full text |Cite
|
Sign up to set email alerts
|

Interpolation of animal tracking data in a fluid environment

Abstract: SUMMARY Interpolation of geolocation or Argos tracking data is a necessity for habitat use analyses of marine vertebrates. In a fluid marine environment,characterized by curvilinear structures, linearly interpolated track data are not realistic. Based on these two facts, we interpolated tracking data from albatrosses, penguins, boobies, sea lions, fur seals and elephant seals using six mathematical algorithms. Given their popularity in mathematical computing,we chose Bézier, hermite and cubic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
125
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(127 citation statements)
references
References 33 publications
1
125
0
1
Order By: Relevance
“…In order to obtain data that were equally spaced temporally, we interpolated consecutive ARGOS hits every 12 h following the methods of Tremblay et al (2006). We determined multiindividual utilization distributions (UDs) with a Gaussian kernel density analysis of the positions from tracks from each habitat.…”
Section: Methodsmentioning
confidence: 99%
“…In order to obtain data that were equally spaced temporally, we interpolated consecutive ARGOS hits every 12 h following the methods of Tremblay et al (2006). We determined multiindividual utilization distributions (UDs) with a Gaussian kernel density analysis of the positions from tracks from each habitat.…”
Section: Methodsmentioning
confidence: 99%
“…Satellite positions were filtered using the 'Argosfilter' package for R (Freitas 2012), which first removes all records with invalid locations (class Z), then all locations that require unrealistic swimming speeds (maximum 2.3 m s −1 ), and finally removes all spikes with angles <15 and 25° if their extension is higher than 2500 and (Freitas et al 2008). Because raw Argos positions are biased by satellite orbital parameters and the penguins' latitudinal positions (Georges et al 1997), we used a linear interpolation algorithm (Tremblay et al 2006) to create a temporally uniform distribution of locations every 15 min along each foraging track. Because of the differences in temporal resolution between the dive (1 s) and location data (15 min, after interpolation), we used temporal proximity to assign an approximate geographic location to each dive.…”
Section: Investigation Of Adélie Penguin Foraging/chick Provisioningmentioning
confidence: 99%
“…Because of some irregularity in GPS signal acquisition, occasional missing locations and the need to calculate speed within discrete intervals, we found it necessary to interpolate regular locations prior to implementing the HMM. We used a curvilinear interpolation, which typically produces more realistic estimates of animal movements than linear interpolation [26] and is less prone to underestimating path length and speed. Our tests indicated that it performed well in recreating GPS data recorded at a higher resolution (see the electronic supplementary material).…”
Section: At-sea Behaviourmentioning
confidence: 99%